Mechanical, Morphological and Thermal Properties of SEBS, SIS and SBR-type Thermoplastic Elastomers Toughened High Impact Polystyrene - TAŞDEMİR, MÜNİR (TAYLOR & FRANCIS INC, 2012)
In this article the effect of PS on the mechanical, thermal and morphological properties of SEBS, SIS and SBR type elastomers-based material was investigated in flow direction 0 degrees and flow direction 90 degrees. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM), Differential scanning calorimeter (DSC) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, SEBS/PS, SIS/PS and SBR/PS polymer blends were subjected to examinations to obtain their elasticity modulus, yield strengths, strength at break, elongation at break, hardness, Izod impact strength, wear rate, melt flow index (MFI), vicat softening point and heat deflection temperature (HDT). In two directions, with the increased amount of HIPS in SEBS/HIPS/CaCO3, SIS/HIPS/CaCO3 and SBR/HIPS polymer blends, the elasticity modulus, yield strengths, strength at break, hardness, Izod impact strength, MFI, HDT, vicat value and wear rate of the resultant material increased, whereas the elongation at break decreased.
Keywords: High impact polystyrene; Polymer blends; Styrene butadiene rubber; Styrene ethylene butadiene styrene; Styrene isoprene styrene; Thermoplastic elastomer; STYRENE-BUTADIENE-RUBBER